HAK CERAI BAGI PEREMPUAN DAN FAKTOR PENYEBABNYA: DIVORCE RIGHTS FOR WOMEN AND CAUSING FACTORS - Fadillah, Rahmat; Syahruji, Syahruji (Mitsaqan Ghalizan, 2023)
The phenomenon of lawsuits for divorce in Indonesia is increasing from year to year. Laws and regulations also accommodate divorce rights owned by a wife. This is also in line with Islamic law which also substantially provides the right to file a lawsuit. This study uses a normative-juridical approach, namely an approach that is guided by laws and regulations, theories, and concepts. The results of this study indicate that women also have the right to divorce, but based on strong reasons, and these reasons are in accordance with applicable law, especially Islamic law. As for why the reason appears in the household ark is due to several factors. One side of the reason for the high number of contested divorces cannot be separated from the better understanding of women regarding their rights as wives in the household. The main factors that are the reasons for wives to carry out divorces are disharmony, husbands not fulfilling their obligations (including the economy), persecution, moral crises, interference from third parties, and unhealthy polygamy. Besides that, several other reasons are not dominant.